2020
DOI: 10.3390/w12082140
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hydro–Climatic Trends in the Mountainous Kofarnihon River Basin in Central Asia

Abstract: Hydro–climatic variables play an essential role in assessing the long-term changes in streamflow in the snow-fed and glacier-fed rivers that are extremely vulnerable to climatic variations in the alpine mountainous regions. The trend and magnitudinal changes of hydro–climatic variables, such as temperature, precipitation, and streamflow, were determined by applying the non-parametric Mann–Kendall, modified Mann–Kendall, and Sen’s slope tests in the Kofarnihon River Basin in Central Asia. We also used Pettitt’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…In our previous study, we demonstrated the seasonal trend analysis of temperature, precipitation, and streamflow upstream of the KRB. Those results were compared with the fifth assessment report (AR5) of the Intergovernmental Panel on Climate Change (IPCC) [79]. The results of the annual temperature, annual precipitation, and annual potential evapotranspiration during the 1950-2016 time period are shown in Table 3.…”
Section: Trend and Change Point Analysis Of The Temperature Precipitation And Potential Evapotranspiration Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we demonstrated the seasonal trend analysis of temperature, precipitation, and streamflow upstream of the KRB. Those results were compared with the fifth assessment report (AR5) of the Intergovernmental Panel on Climate Change (IPCC) [79]. The results of the annual temperature, annual precipitation, and annual potential evapotranspiration during the 1950-2016 time period are shown in Table 3.…”
Section: Trend and Change Point Analysis Of The Temperature Precipitation And Potential Evapotranspiration Seriesmentioning
confidence: 99%
“…In our previous study, we demonstrated the seasonal trend analysis of temperature, precipitation, and streamflow upstream of the KRB. Those results were compared with the fifth assessment report (AR5) of the Intergovernmental Panel on Climate Change (IPCC) [79].…”
Section: Trend and Change Point Analysis Of The Temperature Precipitation And Potential Evapotranspiration Seriesmentioning
confidence: 99%
“…River flow is mainly influenced by snowmelt, since a major part of the annual precipitation falls during the winter months, in higher areas, as snow. A seasonal and annual temperature and precipitation trend analysis of the flat and mountainous areas of Tajikistan can be found in our previous study [40]. In the upstream reaches of the Vakhsh River, due to limitations in the availability of suitable land, irrigation is rather limited.…”
Section: Study Areamentioning
confidence: 91%
“…Mountains rich in biodiversity and ecosystem services contribute considerably to economic activities, for example, through hydroelectricity generation and through tourism, agriculture, and animal husbandry. (20)(21)(22) These essential ecosystem services also characterize regional climates. However, these ecosystems face anthropogenic pressures caused by high population growth and global warming, which further lead to changes in the hydrological cycle and the retreat of glaciers.…”
Section: Overview Of the Research Areamentioning
confidence: 99%